IMPLEMENTASI METADATA DALAM PENGELOLAAN UMKM DI ERA DIGITAL - Armita Isnaini Munthe; Fitri Ramadani; Sindy Aulia Sari; Nurbaiti Nurbaiti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the implementation of metadata in the management of Micro, Small, and Medium Enterprises (MSMEs) to enhance the efficiency and effectiveness of business data management. The research employs a qualitative approach with case studies on several MSMEs that have adopted metadata systems in transaction recording, inventory management, and digital marketing strategies. The findings indicate that the use of metadata enables more structured data management, improves business information accuracy, and accelerates decision-making processes. Furthermore, the integration of metadata with digital technology helps MSMEs optimize marketing strategies and expand market reach more effectively.